Prevalence of neurocognitive deficits in patients with first-episode schizophrenia in an African sample and its relationship with dimensions of psychopathology and psychosocial outcome - Onyekachi Kingsley Ugwuonye; Justus Uchenna Onu; Theclar Ogochukwu Iyidobi; Jude Uzoma Ohaeri (BMC Psychiatry)
Abstract Background Current evidence supports the idea that neurocognitive deficits (NCD) constitute a core dimension of schizophrenia. Studies on longitudinal changes in neurocognition among neuroleptic-naive first-episode schizophrenia (FES) from Africa are uncommon. We aimed to highlight the prevalence of, and changes in NCD among FES on naturalistic treatment follow-up for 8 weeks, and the relationship with psychopathological and psychosocial outcomes. Methods Consecutive FES and Healthy Control (HC) were recruited. Diagnosis of schizophrenia was based on ICD-10 criteria. The HC (n = 86) consisted of nursing students in the same facility, recruited purposely to match the cases in age and gender. After the baseline assessment, 82 FES were followed up 4-weekly for changes in NCD, psychopathological and psychosocial ratings for a period of 8 weeks, using the 3 alternate forms of the Screen for Cognitive Impairment in Psychiatry (SCIP), the Wisconsin Card Test, the Mini Mental State Examination, as well as the Brief Psychiatric Rating Scale, the WHO Disability Assessment Scale, and the Global Assessment of Functioning scale. The control group was tested only once, and their scores were utilized for comparison with the patients’ scores only at week 8. The prevalence of neurocognitive deficits in the two groups was described using percentages and 95% confidence interval. Predictors of cognitive function was determined using multivariate linear regression. Results The prevalence of any NCD among FES at 8 weeks and HC was 62.9% (95% CI: 51.5%, 74.2%) and 1.2% (95% CI: 0.0%, 6.6%), respectively. With treatment, there was a significant improvement in cognitive function at each interval of follow-up. At week 8, the prevalence of any NCD among patients in remission was 55.1%. Total SCIP scores at week 8 had significant inverse moderate relationship with the dimensions of psychopathology. Conversely, total SCIP score was strongly positively correlated with functioning (rhos= 0.71, p < 0.001) at week 8. At week 8, the baseline predictors of total SCIP score were, duration of untreated psychosis (β = -0.33, p = 0.01, variance = 19.8%), negative symptoms (β = -0.35, p = 0.03, variance = 4.9%) and positive symptoms (β = -0.43, p = 0.01, variance = 4.8%). Conclusion The high prevalence of NCD when patients were in remission indicates that they are enduring and merit consideration as a domain of psychopathology.